New mutations in the PKD1 gene in Czech population with autosomal dominant polycystic kidney disease - Merta Miroslav; Lnenicka Petr; Kebrdlova Vera; Svobodova Stanislava; Reiterova Jana; Stekrova Jitka; Viklicky Ondrej; Kohoutova Milada (BMC, 2009)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary renal disease. The disease is caused by mutations of the PKD1 (affecting roughly 85% of ADPKD patients) and PKD2 (affecting roughly 14% of ADPKD patients) genes, although in several ADPKD families, the PKD1 and/or PKD2 linkage was not found. Mutation analysis of the PKD1 gene is complicated by the presence of highly homologous genomic duplications of the first two thirds of the gene. Methods The direct detection of mutations in the non-duplicated region of the PKD1 gene was performed in 90 unrelated individuals, consisting of 58 patients with end-stage renal failure (manifesting before their 50th year of life) and 32 individuals from families where the disease was clearly linked to the PKD1 gene. Mutation screening was performed using denaturing gradient gel electrophoresis (DGGE). DNA fragments showing an aberrant electrophoretic banding pattern were sequenced. Results In the non-duplicated region of the PKD1 gene, 19 different likely pathogenic germline sequence changes were identified in 19 unrelated families/individuals. Fifteen likely pathogenic sequence changes are unique for the Czech population. The following probable mutations were identified: 9 nonsense mutations, 6 likely pathogenic missense mutations, 2 frameshifting mutations, one in-frame deletion and probable splice site mutation. In the non-duplicated region of the PKD1 gene, 16 different polymorphisms or unclassified variants were detected. Conclusion Twenty probable mutations of the PKD1 gene in 90 Czech individuals (fifteen new probable mutations) were detected. The establishment of localization and the type of causal mutations and their genotype phenotype correlation in ADPKD families will improve DNA diagnosis and could help in the assessment of the clinical prognosis of ADPKD patients.